ARE MONETARY AUTHORITIES’ ACTIONS (MONEY SUPPLY) FACTORED INTO NIGERIA’S GOVERNMENT REVENUE STREAMS? - C. STANLEY UDEGBULE; ESTHER ESERA (International Studies Journal)
Conducting a study on the long-run relationship between money supply and government revenue is crucial for informing monetary-fiscal policy decisions in Nigeria as a developing country. This study analyses the dynamic interaction between money supply (using broad M2) and government revenue, using an autoregressive distributive lag (ARDL) bounds test approach from 1980 to 2020. Results from the analyses show the existence of a long-run correlation between supply and government revenue, when money supply was made the explanatory variable. Using government revenue as the independent variable, there was no evidence of long-run relationship in the analyses. By implication, change in government revenue in the previous years have significantly affected money supply as an economic indicator in the Nigerian economy. In addition, the estimated coefficient of revenue indicates a positive and significant impact on money supply within the period of this study. Specifically, a one percent (1%) increases in revenue caused an approximately 0.96% increase in money supply at the long-run. The result equally revealed that, the signs of the short-run dynamic impact of the variable are significant. The ECM is estimated as 0.17% and -o.28%, which implies that government revenue and money supply have significant short-run effect on the Nigerian economy, as against some of the findings of the literature reviewed. The study recommends that, since the oil sector seems to be generating more revenue to stimulate productivity and encourage other sectors, policy makers should introduce measures to effectively monitor and regulate oil production to ensure transparency and accountability.